(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The technological process of cotton cleaning is one of the main processes that determines the quality of the fiber. The technology of cleaning cotton raw materials is used depending on the grade of cotton, that is, the degree of cleaning, the degree of cleaning depends on the viscosity coefficient of the cotton grade.